In Vivo Bioequivalence Study of Drug: An Analysis of Registration in Vietnam Period 2012-2022 - Thanh Hai, Nguyen; Hung, Tang Quoc; Bich Ngoc, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2023)
After more than 10 years of implementation of in vivo Bioequivalence study, there are 835 Bioequivalence drugs licensed to manufacture in Vietnam, accounting for 77.89% of Bioequivalence drugs licensed to circulate on the Vietnamese pharmaceutical market in the period 2012-2022, a worthwhile result. An achievement in the development of In vivo Bioequivalence study in recent years is that the state management agency (Ministry of Health) has increased the required active ingredients to submit bioequivalence study reports for drug registration in Vietnam from 12 active pharmaceutical ingredients to 26 active pharmaceutical ingredients. In the next few years, this number will gradually increase. Therefore, the Government should introduce promotion, development, and preferential policies for enterprises to invest in these ingredients. This paper aims at providing Vietnam pharmaceutical enterprises with an overview of information on the current state of bioequivalence drugs license in Vietnam; supporting the implementation of these studies in practice. Keywords : Bioequivalence, BABE, BE, Regulations, Registration.